USE OF TEAMS GAMES TOURNAMENT TO INCREASE STUDY RESULT AND STUDENT’S CHARACTER ON NEWTON COURSES - Tarita Aprilani Sitinjak (Jurusan Pendidikan Teknologi dan Kejuruan, FKIP, Universitas Palangkaraya, 2014)
To increase of study result and to develop character is one of the goals in the universIty. Academically, this research tells about the implementation of the use of Cooperative Learning type Teams Games Tournament intent to increase the study result and student’s character in Study Programme of Building Technical Education, FKIP, Palangka Raya University, who took Physic Course. Interview, observation and student woorksheets were used as research instruments in order to colect data. From the analysis it is concluded that before cooperative Learning methode type Teams Games Tournament was apllied the student’s study result was low, which shown 78,57 % student failed to accomplish, which the lowest score is twenty and the highest is seventy. The average score of study result in first cycle is 57,14 and the percentage of completion is 40,91% nine student, not complete 59,09%. The highest score in cycle 1 is 78 and the lowest is 43. From Cycle 2 it is concluded that the average score is 70,69 with the completion percentage is 86,36%, with the highest score is 92 and the lowest is 52.